Improvement of Body Satisfaction in Older People: An Experimental Study - Sánchez-Cabrero, Roberto; León-Mejía, Ana C.; Arigita-García, Amaya; Maganto-Mateo, Carmen (Frontiers in Psychology, 2019)
Aging typically manifests itself in a variety of physical and cognitive alterations and challenges that are not always easily accepted. Feeling dissatisfied with these changes can also affect the mood and self-esteem of older people causing body image problems. The present study focuses on body satisfaction in Spanish older people (176 participants; M and SD=64.03 ±1 8.06; age range 50 to over 75) by employing experimental research to test whether psychosocial interventions may have a positive impact. Our aims are threefold: (1) To describe the body satisfaction of older people considering intervening variables, such as age, gender, having a stable partner, time of the year, and place of residence; (2) to compare body satisfaction improvement in older people participating in a specific body satisfaction program designed for this purpose versus a non-specific program run by the Spanish Red Cross; and 3) to examine the relationship between age, gender, having a stable partner, time of the year, place of residence, body satisfaction and participating in the experimental condition. The IMAGINA specific body image program yielded a significant improvement in body satisfaction when compared with the non-specific program in both men and women regardless of marital status and in some age groups: 50 to 54 years old, 60 to 64 years old, and 65 to 69. Male participants, as well as singles, were more satisfied with their bodies, and the contrary was true for divorced and separated. The IMAGINA program was particularly useful in participants with more body image problems. As shown, the pressure to fit beauty standards and related problems do not go away with age, a fact that is embodied and experienced differently in men and women.